Estudio de la oferta turística y su aporte al desarrollo económico de la ruta del rio, año 2022 - Cedeño Mendoza, Heydi Anabel (2022)
The present investigation seeks to focus on the tourist offer that La Ruta del Río promotes to all those who visit the city of Quevedo, and on the contribution to economic development that is one of the main objectives within the tourism sector to encourage social growth, local, and labor. Quevedo is one of the main cities belonging to the province of Los Ríos, which is constantly innovating in tourism, opening up different ventures where you can enjoy cultural, adventure and family tourism within the city of Quevedo. In this context, the analytical bibliographic method was used that allowed analyzing each of the proposed objectives, in addition, the surveys were applied to residents and visitors to obtain the results. From the results it was detected that the tourist offer of the River Route has a great reception by tourists. However, 33% of those surveyed state that there is a lack of tourist security, being a factor that prevents the greater reception of the undertakings in the Ruta del Río, on the other hand, the lack of public lighting was evidenced, which is one of the limitations for the growth of tourism development in the city.